Variables De Afrontamiento Y Psicológicas Explicativas De La Ansiedad Escénica En Instrumentistas De Viento Metal - Francisco Javier Zarza-Alzugaray; Oscar Casanova; Santos Orejudo (European Scientific Journal, ESJ, 2016)
In the process of musical learning, one of the biggest problems that students must face is stage anxiety. This problem can even lead to the abandonment of studies or lead students to adopt addictive behaviours related to the use of substances to mitigate the harmful consequences that stage anxiety can cause. In this study and taken into account the triple vulnerability system described by Barlow (2000) the presence of higher or lower levels of anxiety is explained from personal characteristics such as helplessness, sensitivity to punishment or dispositional optimism. Thus, it is also studied how these constructs are related to the existence of thoughts of abandonment of musical studies, as well as to the existence of behaviours related to the consumption of substances to mitigate the effects of stage anxiety. It becomes clear how helplessness is a key mediating factor between personal and contextual characteristics in order to generate higher or lower levels of stage anxiety. For this study has been gathered a sample of students of metal wind instruments from 6 different centres of Spanish higher education. In this sense we consider that more research is necessary, with other types of instrumentalists in order to study if there are differences between them that could suggest the application of specialized training plans in the future.